Validation of the Optimality Index‐US for Use in Turkey to Assess Maternity Care. (4th October 2013) - Yucel, Cigdem; Low, Lisa Kane; Taskin, Lale
Abstract : Aim: To determine the validity of a translated version of the Optimality Index‐United States (OI‐US) for use in Turkey by comparing the scores for healthy and high‐risk pregnant women. Background: The OI‐US is a validated instrument used in perinatal outcomes research based on the principle of using the least amount of intervention to promote maximum outcomes. It includes process and outcome items in 2 parts, the perinatal background index (PBI) and optimality index (OI) which combine as the total OI‐US. There are not validated instruments for use in Turkey that measure optimality. Methods: The study was conducted at a women's hospital in Ankara, Turkey in April and May 2012. Laboring women (N = 300) were grouped according to their pregnancy risk status into 2 groups: 150 healthy pregnant women and 150 high‐risk pregnant women. Data were collected prospectively and were analyzed with percentages and t tests for independent samples. High scores indicate greater optimality. The total OI includes both the PBI and the OI combined. Results: There was a significant difference between the mean PBI scores in high‐risk and healthy pregnant women (t: 2.654; P < 0.05) and a significant difference between the mean OI scores in high‐risk and healthy pregnant women (t: –2.065; P < 0.05). Yet the total OI scores for high‐risk compared to healthy women was not significant (t: –0.084; P > 0.05). Discussion: The results of this study indicate that while the risk status of women differs, the type of care they received is essentially the same as measured by the Turkish version of the OI‐US which is not optimal. The validity of the instrument appears to function appropriately.